El recurso de casación ante el neoconstitucionalismo garantista: crítica filosófica y constitucional de una casación “de minimis” (Tema Central) - Izquierdo Franco, Pedro José (2015)
This article proposes a critical analysis of an ever more frequent practice of the cassation chambers of the National Court of Justice, here called “de minimis cassation”, by which it is considered sufficient to deny admission or reject a cassation appeal on the mere consideration that the charges contained in it have not been correctly argued under the ground of cassation that the chamber considers adequate in each case. The thesis of this article is that this practice is based on a vitiated conception of cassation and violates the right to effective means of redress in its manifestation as the right to an action and the related pro actione principle, in accordance with the understanding of these contained in the jurisprudence of the Constitutional Court and in legal scholarship.